Vernacular garden as urban landscape element (сomparative analysis of Kyiv and Prešov cases) - Butsykina, Yevheniia (Ukrainian Cultural Studies, 2024)
Background. The aim of the paper is to compare the vernacular gardening within urban landscapes in Ukraine and Slovakia through its ability to enhance resident engagement and reduce levels of indifference and alienation. Methods. I apply Lehtinen's idea of urban aesthetics as a compromise, highlighting the significance of engaging with city imperfections to achieve urban harmony, as well as Jackson and von Bonsdorff offer contrasting perspectives on the landscape concept and urban environment, respectively. Cureton introduces the concept of "vernacular landscape," while Macauley emphasizes the embodied experience of walking in the city. Fenner's insights on gardens enrich the discussion by highlighting their historical resonance and aesthetic allure. Additionally, the text explores the interdisciplinary approach to analyzing vernacular gardens, drawing on concepts from Foucault and Heidegger to provide a comprehensive understanding of their socio-cultural and aesthetic significance within urban landscapes. Results. Vernacular gardens in Kyiv's Rusanivka microdistrict play significant role in intertwining private and public spaces through the lens of care. Amidst the backdrop of war in Ukraine, these gardens symbolize resilience and resistance. Contrasting vernacular gardening practices in Kyiv and Prešov , it highlights their distinct characteristics reflective of their urban landscapes, with Kyiv gardens representing individual initiatives against Soviet traditions and Prešov gardens seamlessly integrating into the urban fabric with a focus on post-Socialist architecture and individual creativity. Conclusions. The study of vernacular elements of the urban landscape, in particular – the vernacular garden and the practice of vernacular gardening, implemented through a combination of different approaches and disciplines: urban, negative and phenomenological aesthetics, cultural anthropology and cultural studies around the landscape, vernacular landscape and cityscape, as well as practical interview methods and walking the combination of different approaches made it possible to define a vernacular garden precisely as a place created by a creative subject within the urban landscape. It acquires the status of a heterotopia and a place that allows you to get involved in the urban environment, identify with it and feel its atmosphere.
Keywords: atmosphere; city; environment; garden; urban landscape; vernacular